(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Performance Appraisal (PA) is gradually becoming a part of a more strategic move towards integrating HR practices and organizational objectives and might now be seen as a general term covering a range of actions through which organizations seek to measure employees and increase their competence, improve performance and distribute rewards. Globalization has created a niche to sustain and enhance human resource since they are the prime contributors to organizational performance. In this 21st century, human development is focused at hiring, training and retaining them. Retaining its valuable and talented employees becomes a major challenge for organisation if they do not know how to motivate them. This paper is aimed providing a review on the various performance appraisal techniques practiced in Indian economy. This paper also highlights literature review on effectiveness of the PA system in various Indian industries.